Allelic variation and effects of earliness per se (Eps) genes in wheat cultivars of Pakistan - Iltaf, Benish; Qayyum, Humaira; Suleman, Hafiz Muhammad; Raza, Ali; ur-Rehman, Sana; Khalid, Hamna; Abbasi, Kainat; Tanvir, Kinza; Mukhtar, Misbah; Zulfiqar, Sima; Kazi, Abdul Mujeeb; Rasheed, Awais (International Journal of Applied and Experimental Biology, 2024)
Optimization of the flowering time in wheat is an important breeding target for its adaptability in target environments. Flowering time is controlled by vernalization, photoperiod, and the relatively poorly characterized earliness per se (Eps) genes. When vernalization and photoperiod criteria are met, Eps genes account for the variance in flowering time. The objective of the study was to decipher the allelic variations for Eps genes in the wheat cultivars of Pakistan and draw their association with agronomic traits. The wheat cultivars released prior to 1965 had an average flowering duration of 82 days, whereas the cultivars released between 1965 and 2000 had an average flowering time of 79 days and 81 days, respectively. Kompetitive allele-specific PCR (KASP) markers were used to genotype all these cultivars for TaElf3-B1, TaElf3-D1, and TaMOT1-D1 genes. For the gene TaElf3-B1, allele Cadenza-type had a frequency of 61.71%. For the gene TaElf3-D1, the proportion of its respective major alleles was recorded, i.e., deletion had a frequency of 72.94%, and Savannah-type was 86.04%. For the gene TaMOT1-D1, the allele Wild-type was found in 55.88% accessions. The gene Elf3-B1 had a significant allelic effect for grain yield (GY), TaElf3-D1 for grain length, and TaMOT1-D1 for GY. Among the wheat cultivars, high percentage (56.89%) of the Savanah-type allele was associated with early flowering. However, the Wild-type alleles (43.1%) were observed to have low allelic frequency, and they were associated with late flowering. This study may allow wheat breeders to make genetic selection of wheat cultivars that are most suited to target environment, ensuring better yield and adaptability.